Validation of Analytical Method for Aeromonas hydrophila Identification using Analytical Profile Index (API) 20E KIT Method - Artati, Diah; Oman, Mohammad; Supriyanto, Supriyanto; Sukarta, Dede; Robisalmi, Adam (Universitas Airlangga, 2024)
The high demand for fish consumption has an impact on increasing aquaculture productivity and causes the vulnerability of increasing bacterial populations in aquaculture fields, so more rapid handling is needed. The use of phenotypic KIT methods (API 20E) has been applied as a targeted and efficient identification support in targeting better bacterial identification accuracy but often provides unequal results. Method validation is one of the general requirements for the competence of a laboratory evaluation: to provide coherent, interpretable, and accurate results with known uncertainties. The purpose of this study was to validate the API 20E KIT method for the identification of A. hydrophila. The conventional method used as a reference is SNI 7303.1:2015. The validation parameters consisted of determining the limit of detection, sensitivity, and specificity tests, as well as the positive predictive value and negative predictive value. The results showed that the limit of the detection value of the API 20E KIT was at a concentration of 100 CFU/mL with an ID of 99.00%. The sensitivity and specificity values in the positive and negative target samples were 100% with a positive predictive value and a negative predictive value of 0%, respectively. In conclusion, the API 20E KIT method as an alternative test method or rapid test was proven valid for identifying A. hydrophila by the test results using the reference method.